Mengamati Perilaku Merokok pada Masyarakat Batang Kilat, Kelurahan Sei Mati, Medan Labuhan Tahun 2023 - Nurhayati, Nurhayati; Andina, Adelia; Wijaya, Arini Aisyahfira; Siregar, Fatimah Azzahra; Nurcholis, M. Hari; Alifah, Syafirda; Irsyad, M. Iqbal; Andini, Fauziah Siti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to determine the percentage of the population that actively smokes and to demonstrate the behavior of coastal communities in the Sei Mati Medan Labuhan Village related to health. To achieve this goal, the researcher used a quantitative descriptive method by administering questionnaires to informants or the public to calculate, present, and percentage the number of people regarding smoking behavior. The analysis technique was conducted through interviews with questions that had been prepared in the questionnaire. The research results indicate that out of 30 samples taken from coastal communities, 60% of the respondents are active smokers, with the majority being 20 years old. The supporting factor for public health education strategies in the Sei Mati Medan Labuhan Village is the high number of active smokers in the coastal area and its connection to driving behavior in the community itself.